ES risks and shareholder voice - He, YE; Kahraman, B; Lowry, M (Oxford University Press, 2023)
We examine whether shareholder votes in environmental and social (ES) proposals are informative about firms’ ES risks. ES proposals are unique in that they nearly always fail. We examine whether mutual funds’ support for these failed proposals contains information about the ES risks that firms face. Higher support in failed ES proposals predicts subsequent ES incidents and the effects of these incidents on shareholder value. Examining the detailed records of fund votes, we find that agency frictions between a group of shareholders contribute to proposal failure.